Tourism Gentrification in Urban Africa: Towards a Research Agenda - Anele Horn; Gustav Visser (Studia Periegetica)
Gentrification and the processes underlying its origin and evolution have been the subject of extensive much research, which has suggested various explanatory mechanisms or triggers of gentrification, including the impact of tourism. The study considers the relevance of tourism-induced gentrification in urban Africa and its possible consequences for tourism development and neighbourhood change in urban areas. According to the authors, tourism-induced gentrification occurs in a small number of African urban areas and is characterised by exclusionary practices that are similar to those that can often be observed in cities of the global North. A number of research avenues are proposed that consider the role of tourism-based development in urban Africa.